2019
DOI: 10.1007/s11033-019-04671-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rilpivirine, 17β-estradiol and β-naphthoflavone on the inflammatory status of release of adipocytokines in 3T3-L1 adipocytes in vitro

Abstract: Rilpivirine is a non-nucleoside reverse transcriptase inhibitor, recently developed as a drug of choice for initial anti-retroviral (ARV) treatment of HIV-1 infection, whereas estradiol is a major component of hormonal contraceptives. Both drugs have effects on lipid metabolism, impairment of adipocyte differentiation and alteration of adipose tissue distribution and function. This study investigated the effects of different concentrations of either rilpivirine or estradiol either alone or in combination on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In contrast with leptin, adiponectin consistently shows anti-inflammatory effects in a number of studies, converging at the mechanism that adiponectin suppresses the production of TNF-α and IFN γ by negatively regulating macrophages and dendritic cells and inhibiting NF-κB activation [ 95 , 96 , 97 ]. While the expression and secretion of adiponectin are inhibited by TNFα and IL-6 as a counteraction from proinflammatory components [ 98 ], it is interesting to find that estradiol suppresses adiponectin but not leptin expression in 3T3-L1 adipocyte cell line [ 99 ] and that serum adiponectin level is negatively correlated with estradiol level in postmenopausal women, thus bringing up the hypothesis that estrogen may antagonize the anti-inflammatory effect of adiponectin [ 100 ]. Taken together, this explains the clinical observation that the increased levels of leptin and decreased adiponectin secretion are directly associated with breast cancer development [ 101 ].…”
Section: Estrogen Inflammation and Breast Cancermentioning
confidence: 99%
“…In contrast with leptin, adiponectin consistently shows anti-inflammatory effects in a number of studies, converging at the mechanism that adiponectin suppresses the production of TNF-α and IFN γ by negatively regulating macrophages and dendritic cells and inhibiting NF-κB activation [ 95 , 96 , 97 ]. While the expression and secretion of adiponectin are inhibited by TNFα and IL-6 as a counteraction from proinflammatory components [ 98 ], it is interesting to find that estradiol suppresses adiponectin but not leptin expression in 3T3-L1 adipocyte cell line [ 99 ] and that serum adiponectin level is negatively correlated with estradiol level in postmenopausal women, thus bringing up the hypothesis that estrogen may antagonize the anti-inflammatory effect of adiponectin [ 100 ]. Taken together, this explains the clinical observation that the increased levels of leptin and decreased adiponectin secretion are directly associated with breast cancer development [ 101 ].…”
Section: Estrogen Inflammation and Breast Cancermentioning
confidence: 99%
“…It acts as a hormone and plays an important role in modulating glucose and lipid metabolism as an insulin-sensitizing adipocytokine. 18 PLE treatment suppressed the release of adiponectin during differentiation. These results showed that PLE decreased lipid accumulation and the adiponectin concentration.…”
Section: Discussionmentioning
confidence: 91%
“…It acts as a hormone and plays an important role in modulating glucose and lipid metabolism as an insulin-sensitizing adipocytokine. 18…”
Section: Food and Function Papermentioning
confidence: 99%